A Study on Impact of Covid-19 on Job Performance & Job Satisfaction of Employees Engaged in WFH Culture - Sheetal Mahendher; Siddharth Pattanayak (Talenta Publisher, 2024)
Background: Coronavirus (COVID-19), which hit in early 2020, altered people's lives and livelihoods. Objective: The goal of this study was to fill in the gaps by looking into numerous possible determinants of job satisfaction and employee performance while working from home, such as work–life balance and work stress, as well as the influence of COVID-19. Methods: This study is descriptive design, a cross sectional study, the data is collected using primary methods that is widely accepted to measure the job satisfaction and employee performance during working from home. Results: Age of respondent was100% of the respondents belong to the category of the age group 18-30. Gender of the respondents -68.2% of the respondents were male while 31.8 % of the respondents belong to the female category. Occupation of the respondents - 86.4% of the respondents were students while 13.6% belong to the employed category. As the significance value that is .072 so it depicts that Covid-19 has a statistically 0.72 impact on Employee performance. Conclusion: Working from home might be a positive indicator in reaction to the collectivist environment.